Congenital Seminal Vesicle Cyst and Ipsilateral Renal Agenesis (Zinner Syndrome): A Rare Association and Its Evolution from Early Childhood to Adolescence - Aikaterini Kanavaki; Isabelle Vidal; Laura Merlini; Sylviane Hanquinet (European Journal of Pediatric Surgery Reports, 2015)
Abstract Zinner syndrome, the association of congenital seminal vesicle cyst and ipsilateral renal agenesis, is more often reported in adults or older adolescents. We present a case of a boy, followed up in our hospital since birth for right renal agenesis who at the age of 4 years presented a right paravesical cyst on ultrasound. The cyst was initially considered as an ureterocele. The diagnosis of Zinner syndrome was made later, at the age of 15 years by ultrasound and magnetic resonance imaging; at that moment the cyst had increased in size and had changed in aspect. This malformation should be considered in the differential diagnosis of a pelvic cyst in male patients with renal agenesis.